Impacto da infecção subclínica por Escherichia coli enteroagregativa e coinfecções na barreira intestinal e crescimento: um estudo infantil multicêntrico - Urtiga, Virgínia Leyla Santos Costa (2022)
INTRODUCTION: Enteroaggregative Escherichia coli (ECEA) is recognized as an important pathogen that can cause subclinical infections, acute and persistent diarrhea, with a history of outbreaks among children and adults, cases of traveler's diarrhea and in patients infected with HIV. This infection has gained prominence in recent years, especially due to its association with environmental enteric dysfunction, resulting in reduced child growth. OBJECTIVE: To evaluate risk factors, the integrity of the gastrointestinal functional barrier, indicators of inflammation and innate immune response associated with CEEA alone or in combination with other enteric pathogens using molecular diagnosis (TaqMan array) and the impact on infant growth at six months of age in a cohort of children. MATERIAL AND METHODS: A nested case-control study was carried out from a multicenter cohort study (MAL-ED network). To evaluate isolated ECEA infection and co-detection, the cohort was organized into 7 groups as follows: children without detection of pathogens in feces collected during the study period; children with ECEA in feces in any collection; children with CEEA and 1 other pathogen; children with CEEA and 2 other pathogens; children with CEEA and 3 or more other pathogens; children with 1 or 2 different ECEA pathogens; and children with 3 or more pathogens other than ECEA. The main outcome variables were delta Z-scores: length-for-age (LAZ); weight-for-age (WAZ), weight-for-length (WLZ), for secondary outcome, markers were included to evaluate the functional gastrointestinal barrier, inflammation and innate immune response in the first 6 months of age between the study groups. The markers used were urinary excretion of lactulose (L) and mannitol (M), alpha-1 antitrypsin (AAT), myeloperoxidase (MPO), neopterin (NEO). RESULTS: Lower maternal education, income, as well as inadequate hygiene and sanitation, food insecurity, in addition to a higher proportion of days of antibiotic use were associated with infections caused by ECEA and 3 or more co-pathogens compared to all other groups of children (p<0.001; p<0.001, p<0.001, p=0.001, p<0.001 respectively). Intestinal function measured by the urinary excretion rate of L/M was altered, driven by the adjusted z-scores of the percentages of lactulose excreted in urine, being significantly higher in the ECEA group with 3 or more pathogens compared to the group 1 and 2 pathogens without ECEA (p=0.010). Greater information through the MPO can be seen in the ECEA group with 3 or more pathogens compared to the groups 3 or more pathogens without ECEA and the group without pathogens (p<0.001; p=0.013). Subclinical infection in the ECEA group with 3 or more co-pathogens influenced smaller growth deficits as evidenced by the length-for-age Z-score (p=0.004). CONCLUSION: This analysis indicates that more severe damage to the gastrointestinal functional barrier and subsequent reduction in infant growth are associated with environmental enteric dysfunction (EASD), and are often associated with the presence of ECEA combined with other enteropathogens in this studied infant population.